A new species, Cricotopus cataractaenostocicola, living in a cyanobacterial colony on vertical rocky substrates with trickling water film in Japan (Diptera: Chironomidae) - Tachibana, Satoru (Zootaxa, 2022)
Trickling water on nearly vertical rocky substrates is a common feature of mountainous regions of Japan. The thin water film is inhabited by discoid colonies of the cyanobacteria Nostoc. This species resembles the North American Nostoc parmelioides Kützing, which forms ear-like colonies in stream beds and is inhabited by symbiotic chironomid larvae. The Nostoc colony in Japan was inhabited by a chironomid larva inside a ring-shaped burrow in the colony. Morphological analyses suggested that these individuals belong to a new species closely related to Cricotopus spp. symbiotic with Nostoc parmelioides. Here, we described the chironomid species Cricotopus cataractaenostocicola sp. nov. The species was distinguished from other congeneric species mainly by the morphology of male hypopygia. It has an anal point and long setae on the outside of the gonocoxite, and does not have setae near the apex of the inner lobe in the gonocoxite. Almost all the Nostoc colonies contained one large larva or pupa. The outer layer of the chironomid-symbiotic Nostoc colony had an elastic hardness. The 3D computer tomography (3DCT) scan showed a connected network of internal passages that are sufficiently wide to be traversed by the larvae, suggesting that cavities are present for the larvae to pass through. Future studies should investigate the formation of cavities and their purpose. As pioneers in the observation of living organisms using 3DCT, we provided the CT data to the Natural History Museum in Vienna.